2009
DOI: 10.1155/2009/971494
|View full text |Cite
|
Sign up to set email alerts
|

Many nonuniversal archaeal ribosomal proteins are found in conserved gene clusters

Abstract: The genomic associations of the archaeal ribosomal proteins, (r-proteins), were examined in detail. The archaeal versions of the universal r-protein genes are typically in clusters similar or identical and to those found in bacteria. Of the 35 nonuniversal archaeal r-protein genes examined, the gene encoding L18e was found to be associated with the conserved L13 cluster, whereas the genes for S4e, L32e and L19e were found in the archaeal version of the spc operon. Eleven nonuniversal protein genes were not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…Many attributes of archaebacteria and eubacteria are so fundamentally different that, for lack of similar chemical intermediates in the pathway or for lack of subunit composition or sequence similarity, independent origin of the genes underlying those differences is the simplest explanation. Such differences include: (i) their membrane lipids (isoprene ethers versus fatty acid esters) [123], (ii) their cell walls (peptidoglycan versus S-layer) [124], (iii) their DNA maintenance machineries [116,125], (iv) the 31 ribosomal proteins that are present in archaebacteria but missing in eubacteria [126,127] (v) small nucleolar RNAs (homologues found in archaebacteria but not eubacteria) [128], (vi) archaebacterial versus eubacterial-type flagellae [129], (vii) their pathways for haem biosynthesis [130,131], (viii) eubacterial- versus archaebacterial-specific steps in the shikimate pathway [132,133], (ix) a eubacterial-type methylerythrol phosphate isoprene pathway versus an archaebacterial-type mevanolate isoprene pathway [134], (x) a eubacterial-type fructose-1,6-bisphosphate aldolase and bisphosphatase system versus the archaebacterial bifunctional aldolase-bisphosphatase [135], (xi) the typical eubacterial Embden–Meyerhoff  (EM) and Entner–Doudoroff  (ED) pathways of central carbohydrate metabolism versus the modified EM and ED pathways of archaebacteria [136], (xii) differences in cysteine biosynthesis [137], (xiii) different unrelated enzymes initiating riboflavin (and F 420 ) biosynthesis [138], and (xiv) in very good agreement with figure 2 b , different, unrelated, independently evolved enzymes in core pterin biosynthesis [139], to name a few examples. The pterin biosynthesis example is relevant because the cofactors H 4 F, H 4 MPT and MoCo, which are central to the eubacterial and archaebacterial manifestations of the Wood–Ljungdahl pathway are pterins (figure 2 d ), suggesting that methyl synthesis occurred geochemically (non-enzymatically) for a prolonged period of biochemical evolution.…”
Section: Rna and The Code Arose But That Is Not Our Focusmentioning
confidence: 99%
“…Many attributes of archaebacteria and eubacteria are so fundamentally different that, for lack of similar chemical intermediates in the pathway or for lack of subunit composition or sequence similarity, independent origin of the genes underlying those differences is the simplest explanation. Such differences include: (i) their membrane lipids (isoprene ethers versus fatty acid esters) [123], (ii) their cell walls (peptidoglycan versus S-layer) [124], (iii) their DNA maintenance machineries [116,125], (iv) the 31 ribosomal proteins that are present in archaebacteria but missing in eubacteria [126,127] (v) small nucleolar RNAs (homologues found in archaebacteria but not eubacteria) [128], (vi) archaebacterial versus eubacterial-type flagellae [129], (vii) their pathways for haem biosynthesis [130,131], (viii) eubacterial- versus archaebacterial-specific steps in the shikimate pathway [132,133], (ix) a eubacterial-type methylerythrol phosphate isoprene pathway versus an archaebacterial-type mevanolate isoprene pathway [134], (x) a eubacterial-type fructose-1,6-bisphosphate aldolase and bisphosphatase system versus the archaebacterial bifunctional aldolase-bisphosphatase [135], (xi) the typical eubacterial Embden–Meyerhoff  (EM) and Entner–Doudoroff  (ED) pathways of central carbohydrate metabolism versus the modified EM and ED pathways of archaebacteria [136], (xii) differences in cysteine biosynthesis [137], (xiii) different unrelated enzymes initiating riboflavin (and F 420 ) biosynthesis [138], and (xiv) in very good agreement with figure 2 b , different, unrelated, independently evolved enzymes in core pterin biosynthesis [139], to name a few examples. The pterin biosynthesis example is relevant because the cofactors H 4 F, H 4 MPT and MoCo, which are central to the eubacterial and archaebacterial manifestations of the Wood–Ljungdahl pathway are pterins (figure 2 d ), suggesting that methyl synthesis occurred geochemically (non-enzymatically) for a prolonged period of biochemical evolution.…”
Section: Rna and The Code Arose But That Is Not Our Focusmentioning
confidence: 99%
“…Thus, IF-1 and eIF-2 in share an RNAbinding motif with r-protein S1 (Gribskov 1992). An examination of the Archaeal unique r-proteins (Wang et al 2009) showed that many are genomically clustered with genes involved in transcription and initiation. In contrast, the older universal r-proteins are exclusively associated with one another with the single exception of integration with the core subunits of the RNA polymerase.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…5g). While most archaeal r-proteins are organized either within the major conserved operons (α, str, spc, and S10) as in bacteria or in one of 10 archaeal-unique operons, 53 11 archaeal r-proteins are not associated with any specific genomic context. Likewise, L45a and L46a do not appear to be within conserved operon structures, nor associated with any particular genes, although we note that the gene (Saci_1216) encoding the 30S subunit binding protein Rbp18, 52 the ribosome biogenesis factor Gar1, and Ser-tRNA synthetase are in close proximity to L45a, L46a, and L47a (Fig.…”
Section: Identification and Distribution Of Novel S Acidocaldarius Lmentioning
confidence: 99%
“…This finding has been suggested to reflect the increasing coordination in the regulation of transcription and translation that has evolved in archaeal (and eukaryotic) lineages since the separation from bacterial phyla. 53 L45a neighbors the gene for a transcription regulator (Lrs14), whereas L46a is downstream of tflD, encoding the TATA binding protein of the transcription factor TFIID. Similarly, L47a is often found downstream of genes encoding the transcriptional regulator AsnC and the DNAdirected RNA polymerase subunit M (RpoM).…”
Section: Identification and Distribution Of Novel S Acidocaldarius Lmentioning
confidence: 99%